Epitaxial Growth of Topological Insulators on Semiconductors (Bi2Se3/Te@Se) toward High‐Performance Photodetectors. Issue 12 (14th October 2019) - Zhang, Ye; Zhang, Feng; Xu, Yiguo; Huang, Weichun; Wu, Leiming; Dong, Zhijun; Zhang, Yupeng; Dong, Biqing; Zhang, Xiuwen; Zhang, Han
Abstract: Heterojunctions, composed of different materials, are widely explored in optoelectronic devices thanks to their unique advantages, such as high carrier mobility and excellent photoelectronic characteristics. In this work, Bi2 Se3 /Te@Se heterojunctions (Bi2 Se3 /Te@Se) are synthesized through the epitaxial growth of Bi2 Se3 nanosheets (Bi2 Se3 NTs) on tellurium@selenium nanotubes (Te@Se NTs) by using a low‐cost and facile solvothermal process. Bi2 Se3 /Te@Se are further applied in high‐performance photoelectrochemical (PEC)‐type photodetection due to the advantages of broadband optical response and fast carrier relaxation time. The PEC results demonstrate that the as‐prepared photodetectors have pronounced photoresponse behavior from the ultraviolet to visible band with self‐driven ability and excellent long‐term stability. It is anticipated that this work provides a new strategy for epitaxial growth of topological insulators on semiconductors for designing new heterojunctions toward high‐performance optoelectronic devices. Abstract : Bi2 Se2 /Te@Se heterojunctions are synthesized through the epitaxial growth of Bi2 Se3 nanosheet on Te@Se nanotubes. The structure, compositions, and characteristics are systematically investigated. Bi2 Se2 /Te@Se heterojunctions are further applied for photoelectrochemical‐type photodetection. They not only exhibit pronounced photoresponse behavior in the UV‐to‐vis region but also excellent self‐driven ability with long‐term stability in ambient and harsh environments.